Enteroparasites in Riverside Settlements in the Pantanal Wetlands Ecosystem - Patrícia Vieira da Silva; Lucimare dos Santos Maciel; Ludiele Souza Castro; Paula Guerra Murat; Minoru German Higa Junior; Patrícia Honorato Zerlotti; Ana Rita Coimbra Motta-Castro; Elenir Rose Jardim Cury Pontes; Maria Elizabeth Cavalheiros Dorval (Journal of Parasitology Research)
Background. Intestinal parasites are a major source of health problems in developing countries, where socioeconomic, cultural, and environmental conditions contribute in maintaining the biological cycles of various parasites and facilitating their spread. The objective of this study, conducted in Corumbá, Mato Grosso do Sul state, Brazil, was to investigate the occurrence of intestinal parasites in riverside communities in the South Pantanal wetlands and conduct educational interventions focused on health and environmental preservation. Method. In total, 196 stool samples were tested for parasites using the merthiolate-iodine-formaldehyde concentration (MIFC) technique and spontaneous sedimentation and educational activities were carried out. Results. Enteroparasite prevalence was 72% (65.6–78.2%; 95% CI). Of the 141 positive cases, monoparasitism was found in 34.7%, biparasitism in 23%, and polyparasitism in 14.3%. Entamoeba coli was the most frequent protozoan (70.2%). Among helminths, hookworms were the most prevalent. Enteroparasitosis prevalence did not differ for sex or place of abode but proved higher in individuals older than 10 years. Conclusion. The high positivity rate for enteroparasites found for the communities stems from lack of sanitation and poor personal and environmental hygiene habits, indicating that effective health policies and educational interventions are needed to reduce the current risk levels.